Etika Petugas Pajak Dalam Islam - Hakim, Rahmad (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Tax is one source of state income. Therefore the tax return should be managed as well as possible. Nowadays, the condition of tax officer is in less than ideal condition, or even in bad condition, with the rise of corruption practice, tax evasion, selective logging to the taxpayer causing the losses of the State, injustice for the ummah so the loss of belief of ummah to the tax officer itself . This literature research will discuss the ethics of tax officials in Islam. By using content analysis, the author describes the general description of tax in Islam, the terms of the tax officer and the mechanism of tax management in Islam. In this study, the criteria of tax officials in Islam can be categorized into 7 (seven) criteria, among others: (1) not through violence (physical contact) to the taxpayer, (2) have gentle nature (al-'afwu), 3) does not exceed the limits of ability, (4) has a deep knowledge of the object of taxes imposed taxes, (5) taxes with good and right (according to Shari'a), (6) taxes fairly, (7) consider mashlahat All parties (State and taxpayers). Keywords: Tax, Tax Officer, Islamic Sharia